Pengaruh Modal, Jam Kerja, dan Jumlah Tenaga Kerja Terhadap Pendapatan Pengusaha UMKM Berbasis Kuliner Di Kecamatan Banjarmasin Timur - Aditya Prawira; Siti Mutmainah Z (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to find out the characteristics of culinary-based SMEsin the East Banjarmasin sub-district to determine whether assets, operational hours, amountsof workers simultaneously and partially affected the income of culinary-based SMEentrepreneurs in the sub-district of East Banjarmasin.All the respondents in this research are all owners of 22 culinary-based SMEs in thesub-district of East Banjarmasin. The research data was processed and analyzed usingmultiple linear regression analysis methods.The results of the research showed that the assets, operational hours, and amounts oflabor simultaneously affected the income of the culinary-based Small Medium Enterprises(SME) in the sub-district of East Banjarmasin. Assets are the most dominant variable thataffected the income of the culinary-based Small Medium Enterprises (SME) in the sub-districtof East Banjarmasin